2021
DOI: 10.15388/amed.2021.28.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Diverticulum in SARS-CoV-2 Patients on Non-Invasive Ventilation A not so “Spontaneous” Cause of Pneumomediastinum? An imaging Pictorial Presentation of Two Cases with Review of Literature

Abstract: Spontaneous pneumomediastinum is a rare but potentially life-threatening condition, the incidence of which has showed an increase in patients with SARS-CoV-2 pneumonia, especially when they are on positive pressure ventilation. None of the reported cases of covid related pneumomediastinum had an associated tracheal diverticulum. Also, to the best of our knowledge, tracheal diverticulum has not been reported in patients on NIV. We report 2 cases of COVID-19 pneumonia on NIV with pneumomediastinum, which also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The presence of TD can also complicate interventions such as tracheal intubation and administration of positive pressure ventilation since the TD is prone to perforation, giving rise to pneumomediastinum [ 17 ]. A literature review has also revealed cases reported of TD arising after non-invasive ventilation in coronavirus disease 2019 (COVID-19) patients, which had an associated pneumomediastinum [ 5 ]. Regarding this case, no complications or symptoms were reported after the incidental finding was determined to not be a pneumomediastinum but instead a TD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of TD can also complicate interventions such as tracheal intubation and administration of positive pressure ventilation since the TD is prone to perforation, giving rise to pneumomediastinum [ 17 ]. A literature review has also revealed cases reported of TD arising after non-invasive ventilation in coronavirus disease 2019 (COVID-19) patients, which had an associated pneumomediastinum [ 5 ]. Regarding this case, no complications or symptoms were reported after the incidental finding was determined to not be a pneumomediastinum but instead a TD.…”
Section: Discussionmentioning
confidence: 99%
“…Although TDs are considered benign in nature, they are occasionally symptomatic, presenting with cough, dyspnea, frequent respiratory infections, dysphonia, or hiccups [2][3][4]. Additionally, there have been several reported cases of adverse outcomes associated with TD associated with ventilatory support [5][6][7]. This is especially concerning in patients with acquired TD as they are generally a population with chronic lung problems that lead to sometimes invasive ventilatory intervention [1].…”
Section: Introductionmentioning
confidence: 99%
“…In general anesthesia, tracheal diverticula cause failures in tracheal intubation, positivepressure ventilation, and lung isolation [2][3][4]. Additionally, positive-pressure ventilation for tracheal diverticula causes tracheal diverticula rupture, subcutaneous emphysema, and pneumomediastinum [4][5][6][7][8][9][10][11]. Thus, preventing positive-pressure ventilation to tracheal diverticula is important to avoid these adverse events.…”
Section: Introductionmentioning
confidence: 99%